Psychiatric nosological historiography - Part II: psychopharmacology and somatogenic perspectives - Gomes, Marleide de Mota (2023)
Introduction: The history of psychiatry encompasses the evolving concepts about the relationship between body and mind and also of the definiton of normality, which depend on the knowledge and customs of different times and places. For a better understanding of this journey, this study privileged the presentation of the main influential figures on the construction of psychiatric nosology and classifications mainly unfolded on a descriptive or causal basis, from psychics or somatics driving, since the Western Renaissance. This article, the second in a two-part series, mainly discusses the importance of psychopharmacology for a better understanding of mental disorders and their classifications. Part one is a preamble to the historical development of the new nosography and psychopharmacology. Method: Narrative review based on secondary sources. Results: The current article illustrates how the understanding of the pathophysiological mechanisms underlying mental illness improves, mainly employing the psychopharmacology that may lead to the reclassification of certain mental disorders. This natural reductionism view of the sciences must be in cooperation with an integrative understanding of the human being, as is customary in the humanities.  Conclusion: The study of psychiatric nosohistoriography helps to understand the conceptual evolution of mental illnesses and the most recent importance of psychopharmacology for this.